Morgen habe ich eine Überraschung für Dich - Munsinger, Lynn,Lowery Collins, Pat (Lentz, 1992)
When Turtle tells Squirrel he'd like to fly, Squirrel finds a way to help him–much to Turtle's dismay!
Keywords: Flight; German language materials; Squirrels; Turtles